Product and Quotient of Independent Gauss Hypergeometric Variables (2011)
In this article, we have derived the probability density functions of the product and the quotient of two independent random variables that have a hypergeometric Gaussian distribution. These densities have been expressed in terms of the first hypergeometric function of Appell F1. In addition, Rényi and Shannon entropies have also been derived from the Gage hypergeometric distribution.